Comparison of Pain in Patients with Topical Anaesthesia Alone Versus Topical Anaesthesia with Intracameral Lidocaine for Phacoemulsification (Medical Forum Monthly, 2024)
Objective: To compare pain in patients undergoing phacoemulsification with topical anaesthesia alone versus topical anaesthesia with intracameral lidocaine.Study Design: Randomized controlled trials study.Place and Duration of Study: This study was conducted at the Department of Ophthalmology, University Medical & Dental College, Faisalabad, from May 2016 to December 2016.Materials and Methods: It was conducted on patients undergoing phacoemulsification. One hundred and twenty patients were selected in accordance with the inclusion and exclusion criteria. They were divided into two equal groups, group A patients were operated under topical anaesthesia alone while those of Group – B were operated under a combination of topical anaesthesia and intracameral preservative free lidocaine. Visual Analog Scale was used for pain assessment. Data was analyzed using computer software SPSS version 21.0. Mean and standard deviation were calculated for quantitative variables like age and pain. Frequency and percentages were calculated for qualitative variable i.e. gender of the patients. Chi-square test was applied for comparison and a P-Value ≤0.05 was considered as significant.Results: A total of one hundred and twenty patients were selected. Out of them 50.8% were male and 49.2% were female. They were divided into two equal groups A and B, group A patients were operated under topical anaesthesia alone while group B were operated under topical anaesthesia along with intracameral Lidocain. Group A and group B had a mean age of 54.55 ± 8.75 and 56.00 ± 9.01 years respectively. Eightpatients of group A had pain comparedto only 2 patients of group B. This difference is statistically significant with theP value of 0.041.Conclusion: A significant reduction was observed in pain score of patients operated under topical anesthesia with intracameral lidocaine for phacoemulsification as compared to topical anesthesia alone.